Desplazamiento y capacidad de búsqueda del nematodo entomopatógeno nativo Heterorhabditis amazonensis RSC5 (Rhabditida: Heterorhabditida) - Andaló, Vanessa; Furtado Moreira, Grazielle [UNESP]; Moino, Alcides (My University, 2014)
Response of Heterorhabditis amazonensis RSC5 to compounds released by different host insects and its virulence level to several insect hosts like Galleria mellonella, Mycotretus apicalis and Tenebrio molitor were evaluated in this study, and compared with other entomopathogenic nematode species like Steinernema carpocapsae All and Steinernema riobrave 355. Tests were performed in Petri dishes with agar-water 2% to determine nematode movement toward the insect with and without opportunity of choosing different insect hosts. Evaluations were made quantifying the proximity of infective juveniles (IJs) to the insect as a source of allurement. In order to determine the displacement of IJs in a closed soil condition, a test was carried out in an arena with sand. The nematode was virulent to the target insects. When nematode and insect were released on agar-water, IJs moved toward the stimulus, with H. amazonensis showing preference for certain insects. In the arena with sand S. carpocapsae caused lower insect mortality (70% ± 8.9 for G. mellonella) than H. amazonensis and S. riobrave (80% ± 6.5 and 99% ± 0.0). Heterorhabditis amazonensis was able to find and choose its hosts (G. mellonella and T. molitor), similarly to S. riobrave behavior, and located them more effectively than S. carpocapsae. The virulence of H. amazonensis was thus similar to S. riobrave, and this characteristic could be promising to introduce this native species in integrated pest management programs.
Heterorhabditis amazonensis RSC5 (Rhabditida: Heterorhabditidae) movement and host recognition
Keywords: Behavior; Chemical stimulus; Chemoreception; Steinernematidae